An efficient “3 phase 4 channel AC energy meter” with automatic load control and automated billing using GSM (International Journal of Engineering and Computer Science, 2017)
Energy meter reading tedious process. Now a day energy meter reader goes to every premise and takes the readingmanually then issues the bill. In manually reading human error possible and not provide reliable meter reading. To avoid thisdifficult task Automatic Energy Meter Reading (AMR) system is introduced. AMR is the technology that automatically collectingconsumption and status of data from energy metering device and transferring the data to Electricity Board (EB) office by usingWireless Sensor Networks (WSN). After verifying customer‟s serial number bill will be issued then data has been stored intodatabase. The proposed system automatically disconnect meter either load crosses concern limit or payment periods exists. It alsodoes not provide electricity tampering and provide accurate meter reading.